Teleexercise for geriatric patients with failed back surgery syndrome - Alizadeh, Reza; Anastasio, Albert Thomas; Shariat, Ardalan; Bethell, Mikhail; Hassanzadeh, Gholamreza (Frontiers in Public Health, 2023)
Introduction: Failed back surgery syndrome (FBSS) is defined as back pain which either persists after attempted surgical intervention or originates after a spine surgery. There is a high risk of perioperative morbidity and a high likelihood of extensive revision surgery in elderly patients with FBSS or post-laminectomy foraminal stenosis. Methods: Thus, there is a need for safer and less invasive methodologies for the treatment of FBSS, such as patient-tailored exercise training. Results: Due to the high cost of face-to-face services and with attention to the infection mitigation in the wake of the COVID-19 Pandemic, teleexercise (utilizing an internet-based platform for the provision of exercise-related care) may be a practical and cost-beneficial method of exercise delivery, especially for geriatric patients with limitations in mobility and access to care. Conclusion: In this commentary, we will suggest some practical exercise training methodologies and discuss the benefits of teleexercise for geriatric patients with FBSS.